Actual Flight Movements of Electric Helicopters for Making a Disaster Area Monitoring System - Takuya Saito; Kenichi Mase (Institute of Advanced Engineering and Science, 2014)
This paper describes the actual flight movements of electric helicopters and how to implement a disaster area monitoring system using electric ground vehicles and electric helicopters. A quad-rotor helicopter and a hex-rotor helicopter were used in the proposed system, specifically, the AR.Drone 2.0 and the DJI Innovations frame kit with an auto pilot system, respectively. We developed a software framework for the AR.Drone 2.0, which makes it possible to obtain flight data and images and to control automatic flight operations by computer. The relationship between the flight parameters and the real flight movements of the AR.Drone 2.0 were experimentally investigated. In conclusion, we found that the AR.Drone 2.0 with a software framework and a developed hex-rotor helicopter are sufficiently effective in implementing a disaster area monitoring system using electric ground vehicles and electric helicopters.